Imágenes de centauros en los vasos áticos de figuras negras y de figuras rojas - Herranz, María. (Oxford)
[6], 287 sayfa
Keywords: “The centaur, a hybrid being with the body of horse and a human head and torso, first appeared in the mountains of Thessaly. This was the Greek horse-breeding region and it seemed natural for the centaur to have originated there, in the heart of this exclusive heritage of the landed gentry. Centaurs belonged to the spheres of heroic mythology, with clear ties to the values of the aristocracy. This book is composed of a catalogue divided into nine chapters. Each chapter comprises catalogue entries for a number of black-figure and red-figure Attic vases. The division into chapters is based on the various types of centaurs and different conflicts, either among themselves or against a hero. In addition to the catalogue is a chapter on images and statistics. Each of these nine chapters corresponds to a section of catalogue entries and statistics, as the information refers to two examples in each section, one in black figures and another in red figures. The highlighted examples illustrate the variety of different vase types (amphorae, lekythoi, etc.) and their chronology (550-500 BC, 500-450 BC). The statistics are likewise divided into black and red figures, and various themes, such as the centaur Pholos and the banquet, or Herakles and Nessos. For each of these themes or groups of examples, a table is given showing the number of vases (amphorae, lekythoi, etc.) and their place in the chronology (550-500 BC, 500-450 BC, etc.).” --